A Foucauldian investigation of CSR and the concept of responsibility - Engel, Cecile (2015)
Purpose – The dissertation aims to highlight a potential new intellection of CSR – and especially of the concept of responsibility – from CMS theoretical perspectives and Foucault’s theories of sovereignty and governmentality.